Association of early and mid-pregnancy maternal serum uric acid with hypertensive disorders of pregnancy - Zou, Chang; Zhao, Ruru; Liu, Xiaosong; Yang, Yuanyuan; Shen, Qinxin; Du, Qiaoling (Frontiers in Endocrinology, 2025)
ObjectiveTo examine association between maternal serum uric acid (UA) measured during gestational 4–24 weeks and the subsequent development of hypertensive disorders of pregnancy (HDP) in a large Chinese cohort.MethodsThis historical cohort study included 84,298 singleton pregnancies registered at Shanghai First Maternity and Infant Hospital (2013–2022). Serum UA was measured before 24 weeks of gestation. Participants with pre-existing hypertension or incomplete data were excluded. Generalized additive models (GAMs) and multivariable logistic regression analyses were used to assess nonlinear and independent associations between UA levels (quartiles and continuous values) and risks of gestational hypertension (GH), preeclampsia (PE), and overall HDP cases, adjusting for maternal age, pre-pregnancy BMI, education, and glucose metabolism disorders.ResultsUA levels were consistently higher among women who later developed HDP than in normotensive pregnancies throughout gestational weeks 4–24. Higher UA concentrations consistently associated with an increased risk of HDP diseases, the top UA quartile showed the strongest associations with GH (1.82, 1.59–2.08), PE (1.67, 1.48–1.89), and total HDP (1.77, 1.61–1.94). GAM analyses revealed enhanced relation of UA to HDP occurrence from the 4th week to 24th week, and showed specific patterns in GH/PE, predictive strength of maternal UA increased with advancing gestational age.ConclusionsElevated maternal UA levels in early-to-mid gestation independently related to HDP risk, with subtype-specific and gestational-age–dependent patterns. UA serves as a practical potential biomarker for early risk stratification and dynamic monitoring of women at risk for hypertensive complications.